Potential for Islamic Banking in Macedonia: An Empirical Evidence - Abdullahi, Sherif; Shaharuddin, Amir (International Review of Management and Marketing, 2016)
The purpose of this research paper is to investigate the potential for introduction of Islamic banking services in Macedonia. Furthermore, it examines the level of knowledge and awareness on Islamic banking principles and instruments, and the demand and support for Islamic banking services among various banks’ stakeholders in Macedonia. The study adopted a combination of quantitative and qualitative methods. 500 respondents participated in the survey of questionnaires and 16 experts including regulators, bankers, religious scholars and academician were interviewed. Descriptive statistics was used to analyze the questionnaires. Hence, the interpretative method was used to analyze the interviews. The findings indicate solid level of knowledge and awareness on Islamic banking principles and instruments among various banks’ stakeholders. Also, there is a strong demand and support for Islamic banking services among various banks’ stakeholders. Considering the gap found in literature, the need to conduct a research to investigate the need for Islamic banking service in Macedonia is highlighted. In the case of Macedonia, the study could be beneficial for investors and regulators who might think of introducing Islamic banking services in the country. Keywords: Islamic banking, Knowledge and awareness, Demand and support for Islamic banking services, Macedonia JEL Classification: G2